Validação de um manual educativo como tecnologia de enfermagem para pessoas com Diabetes Mellitus tipo 2 - Melo, Ingrid Almeida de (2017)
With the shortage of printed educational manuals developed and validated by nursing focused on guidelines for self-care activities with people with type 2 diabetes mellitus, we chose to develop a methodological development research that aimed to validate an educational manual for People with type 2 diabetes mellitus as nursing technology. For that, the theoretical pole of the theory of psychometry used in Pasquali's model was used. The research was carried out in the diabetes mellitus outpatient clinic of the University Hospital of Sergipe and in the Center of Medical Specialties of Aracaju (CEMAR). The study population consisted of two distinct groups: the expert judges and the target audience. The group of expert judges was divided between professionals in the area of Health and professionals in the areas of Exact (Graphic Design) and Human (Social Communication). The group of health judges was composed of health professionals, including doctors, nurses, nutritionists, physical educators and psychologists, who were responsible for the validation of content and appearance. The second group of judges was composed of professionals, from the area of exact as graphic design and from the area of human as social media that performed only the validation of appearance. The target group was formed by people with type 2 diabetes mellitus, who did the analysis of the appearance. Data collection was done after approval of the Research Ethics Committee of the Federal University of Sergipe. The instruments used in this research were three questionnaires, one for the validation of content and two for the validation of appearance, all adapted from the work of Oliveira (2006). A quantitative analysis of the data and variables of the study was performed, as well as a descriptive analysis of the comments and suggestions given by the judges and the target public. For the presentation of the quantitative data, tables were used, in which the percentages and measures of central tendencies (mean, standard deviation, minimum, median and maximum) of the variables were presented. This analysis was performed through the answers to the questionnaire items applied to expert judges and the target audience. The Content Validity Index (CVI), Cronbach's Alpha Coefficient of the items and Percentage of Agreement (PC) of the blocks were applied in the first and second evaluations. In the validation of the appearance of the target audience, in the two evaluations, the PC> 80% with IVC's> 80%; In the first evaluation, PC <80% and IVC <80% in 12 items, being disapproved by the judges, then the items were analyzed and reformulated, in the second evaluation the PC > 80%, and all items were validated; In the validation of content of the judges in the health area, in the first evaluation presented a PC <80% and most of the items presented the CVIs> 80%, only eight items were reformulated; In the second evaluation all the blocks were valid because they presented a PC> 80% and the items validated because they presented the CVIs> 80% only three items presented the CVIs <80%, but their p-value> 0.05. And in the validation of the health judges' appearance, in the first evaluation there was a PC <80% in three blocks, with twenty-three items validated, only three items were not validated with CVI <80% and p-value < In the second evaluation all blocks were validated, and the approved items, only item 5.5. Presented an IVC <80% but p-value> 0.05. After reviewing the comments and suggestions, the reformulations were made to adapt the manual. Therefore, it is concluded that the manual is valid, and it becomes a valuable material to help autonomy for the care of people with type 2 diabetes mellitus.